Bioactive Compound Contents and Antioxidant Activity of of Fermented Lead Tree (Leucaena leucocephala (lmk.) de Wit) Seeds - Suryanti, Venty; Marliyana, Soerya Dewi; Rohana, Gracia Lasma; Trisnawati, Elyna Wahyu; Widiyanti, Widiyanti (Universitas Jenderal Soedirman, 2021)
Leucaena leucocephala (lmk.) de Wit) (leed tree) seeds have been fermented by Indonesian as a traditional food which is called tempeh. The fermentation products of legume seeds are good functional foods, since they contain many bioactive compounds. The objective of this study was to determine the bioactive compound contents of fermented lead tree seed, such as total phenolic, ascorbic acid, Î²-carotene and a-tocopherol. Antioxidant activity testing was carried out using the thiobarbituric acid reactive substances (TBARS) method. Analysis of total phenolics, ascorbic acid, Î²-carotene and a-tocopherol were carried out using the folin-ciocalteu method, iodine titration, spectrophotometry and iron (III) chloride-thiocyanate, respectively. Rhizopus oligosporus was used to ferment lead tree seeds for 0, 1, 2, 3 and 4 days. Fermented leed tree seed powder was extracted with petroleum ether followed by ethanol. In comparison to unfermented leed tree seed powder, the Î²-carotene and a-tocopherol of the fermented seed powder increased. The greatest enhancement of Î²-carotene and a-tocopherol contents were observed at day 2 of fermentation. The highest antioxidant activities of fermented leed tree seeds were also obained at day 2 of fermentation with 55.55Â±4.59 and 74.46Â±3.49% inhibition in petroleum ether and ethanol extracts, respectively. The results show that lead tree seed tempeh has high antioxidant activity due to the bioactive compounds contains, such as Â phenolics, Î²-carotene and a-tocopherol. Therefore, leed tree seed tempeh could be used for possible commercial production of functional food to alleviate oxidative stress.